2013
DOI: 10.1039/c3cc46957c
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-specific phosphorescent imaging and tracking in living cells with an AIPE-active iridium(iii) complex

Abstract: An AIPE-active iridium(III) complex was found to possess high specificity for mitochondria, superior photostability, low cytotoxicity, and high resistance to the loss of mitochondrial membrane potential. Thus, this complex can be used for mitochondrial imaging and tracking in living cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 30 publications
2
47
1
Order By: Relevance
“…The bond lengths of IreN (ppy) (2.027(5) Å and 2.045(5) Å) were longer than IreC (ppy) (2.010(6) Å and 2.026(7) Å), but shorted than IreN (dmn) (2.140(5) Å and 2.151(5) Å), constructing a distorted octahedral structure. It was similar with the reported crystal structures of cyclometalated Ir(III) complexes [Ir(C ∧ N) 2 (N ∧ N)] þ [27,28].…”
Section: Synthesis and Characterizationsupporting
confidence: 89%
See 1 more Smart Citation
“…The bond lengths of IreN (ppy) (2.027(5) Å and 2.045(5) Å) were longer than IreC (ppy) (2.010(6) Å and 2.026(7) Å), but shorted than IreN (dmn) (2.140(5) Å and 2.151(5) Å), constructing a distorted octahedral structure. It was similar with the reported crystal structures of cyclometalated Ir(III) complexes [Ir(C ∧ N) 2 (N ∧ N)] þ [27,28].…”
Section: Synthesis and Characterizationsupporting
confidence: 89%
“…In previous work [27,28], we have found that some iridium(III) complexes posse high specificity for mitochondria, superior photo-stability and can be used for mitochondrial imaging and tracking without damaging mitochondrial membrane. The specific mitochondrial location of these Ir(III) complexes may also be due to their positive charge that facilitates the mitochondria membrane crossing.…”
Section: Introductionmentioning
confidence: 99%
“…Some cationic cytometalated Ir(III) complexes are known to target mitochondria [42,43]. To assess if a similar behavior was observed with Ir4, (Fig.…”
Section: Intracellular Sulfite Imagingmentioning
confidence: 99%
“…[32] Furthermore, while there have been some recent studies of the cytotoxicity of tris(bidentate) (pyridyl)iridium(III) complexes, they have generally utilised C-metallated ligands. [33][34][35] The results of this study demonstrate that the kinetically inert (in the absence of strong light), non-organometallic, chlorido-bearing poly(pyridyl)iridium(III) complexes, Cl-Irbb n , can have significant cytotoxic properties. The anticancer activity increased with alkane chain length, Cl-Irbb 16 showing the best activity against both cell lines.…”
Section: Discussionmentioning
confidence: 99%